Pemberdayaan Kelompok Wanita Tani dalam Optimalisasi Pekarangan Sebagai Ketahanan Pangan Keluarga - Heny Alpandari; Tangguh Prakoso (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Land yard can still be used optimally to fulfill family nutrition. For the people of Daya Makmur Village, plant cultivation in the yard is a common thing that has been done for a long time. But over time, there was a change in habits in rural communities, where they began to leave the activity of growing vegetables in their yards. In fact, most of the yard was left empty and overgrown with grass. The purpose of this service activity is to regenerate public interest and awareness in cultivating vegetables in the yard to meet family nutrition. The method of activities carried out is survey, counseling and discussion. From the results of the activities that have been carried out, it is concluded that the people of Daya Makmur Village already know the techniques of cultivating vegetable crops and the community is motivated again to plant vegetables in their yards.